Meeting the information needs of the ulama in the digital world: challenges for the Muslim information professional - Abu Bakar, Ahmad Bakeri; Saleh, Adam G. (2010)
The advent of Information and Communication Technology (ICT) and its momentous growth especially in the 21st century, is perhaps the most amazing phenomenon in human history. It has impacted virtually on all aspects of human endeavor, most especially on how information is generated, processed, and disseminated. Individuals have become highly sophisticated, professionalized, and demanding on both the system and the information professionals to satisfy their ever increasing information requirements. While a lot of progress can be seen in efforts being made to meet the needs of various professional groups such as engineers, lawyers, medical practitioners, scientists, administrators etc through the development of specialized databases and tailor-made information retrieval systems (IRS), the Ulama the most influential professional group in the Muslim world, vested with the responsibility of preaching, counseling, administration, and providing religious leadership to the Muslims is neglected. This paper looks at the problems being faced by the Ulama using ICT to search for information to enable them perform their roles effectively. Among several factors identified, lack of a comprehensive Islamic Database and a suitable Information Retrieval System (IRS) is among the factors militating against the use of ICT by the Ulama. The paper challenged Muslim information professionals to come up with suitable data-bases and tailor-made IRS specifically designed to meet Islamic search pattern.